Ignătescu S., Ilkiv М., Rusnak О. Ukrainian-Romanian Stages For Student Archaeological Practice - Rusnak, Oleksandr; Ільків, Микола; Ignatescu, Sorin (Yuriу Fedkovych Chernivtsi National University, 2022)
Cross-border cooperation between institutions of higher education is one of the goals of modern education, an important component of didactic and research activities. Over the past 30 years, such an initiative has been implemented several times during archaeological practices for students of Yuriy Fedkovych Chernivtsi National University and «Ștefan cel Mare» University of Suceava. During this time, four student exchanges took place. The main practice bases in 1993 were the settlements of Chornivka in Ukraine and Târgu Frumos in Romania, in 1994 – the settlements of Revne and Siret, and in 2006 and 2007 – the Khotyn fortress and the settlement of Fetești – La Schit. The periods of joint practice lasted for 10 days, were related to the solution of certain organizational issues and allowed to realize a number of important educational goals.
Keywords: archaeological research, archaeological practice, student exchange, cross-border cooperation, Yuriy Fedkovych Chernivtsi National University, «Ștefan cel Mare» University of Suceava